2020
DOI: 10.4103/ijt.ijt_51_20
|View full text |Cite
|
Sign up to set email alerts
|

More is not always better in hair growth factors. epidermal growth factor: hair growth factor involved in alopecia areata pathogenesis

Abstract: Background: Alopecia areata (AA) is the second most frequent nonscarring alopecia after androgenetic alopecia; the trigger factor induces changes in the growth plate of hair bulb and leads to premature termination of anagen phase. Epidermal growth factor (EGF) can be the key molecule that participates in initiation and suppression of normal hair growth cycle. The role of EGF in the pathogenesis of AA is still uncertain. Aim of the Work: This aim is to estimate the serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…EGF and/or TGF-, which are closely related to ErbB1, can suppress the formation of HF in the early phases of its growth [13]. EGF and EGFR shown the ability to limit hair shaft elongation and convert the morphology to a catagen growth pattern in human HF culture by inhibiting mitotic regulators such Rcc2 and Stathmin 1 [24].…”
Section: Discussionmentioning
confidence: 99%
“…EGF and/or TGF-, which are closely related to ErbB1, can suppress the formation of HF in the early phases of its growth [13]. EGF and EGFR shown the ability to limit hair shaft elongation and convert the morphology to a catagen growth pattern in human HF culture by inhibiting mitotic regulators such Rcc2 and Stathmin 1 [24].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, EGF has been shown to inhibit hair shaft elongation and change the morphology to catagen growth patterns by suppressing mitotic regulators including RCC2 and Statmin1 54,55 . El‐Refai et al also reported that EGF negatively impacts hair follicle growth and may be linked to the pathogenesis of alopecia areata 56 …”
Section: Hair Lossmentioning
confidence: 99%
“… 54 , 55 El‐Refai et al also reported that EGF negatively impacts hair follicle growth and may be linked to the pathogenesis of alopecia areata. 56 …”
Section: Hair Lossmentioning
confidence: 99%
“…35 However, evidence on possible proalopecic action of growth factors is weak compared with the strong evidence of their substantial anti-alopecic effects. 36…”
mentioning
confidence: 99%